The epidemiology of Haemophilus influenzae in healthy carriers and infected in Iceland following the introduction of Protein D conjugated vaccine - Sandra Berglind Tómasdóttir 1994- (2019)
Introduction: Haemophilus influenzae is part of the normal flora of the nasopharynx but can cause a variety of infections, especially in young children and patients with underlying diseases. H. influenzae can express a polysaccharide capsule, six serotypes (a-f) have been identified. Strains without a capsule are called Non-Typeable H. influenzae (NTHi). Antibiotic resistance in H. influenzae has increased for the last decade, especially because of penicillin-binding protein 3 (PBP3) modifications. In 2011 a 10-valent conjugated pneumococcal vaccine (PHiD-CV) was introduced in Iceland, which uses protein D (PD) derived from NTHi as a conjugate. PD is encoded by the hpd gene and is in most H. influenzae. By using PD as a conjugate there is a possibility that the vaccine could provide protection against H. influenzae infections. Aims: The aims of this study were to continue to assess the effects of the vaccination on carriage rate of H. influenzae among healthy children, the prevalence of the hpd gene and each serotype of H. influenzae both in carriage isolates and in clinical samples. Furthermore, to assess the effects on the antimicrobial susceptibility pattern of H. influenzae. Material and methods: Nasopharyngeal samples were obtained from healthy children attending 15 DCCs in the Reykjavik capital area of Iceland (2009, 2012-2018). H. influenzae isolated from clinical samples from the middle ear (ME), lower respiratory tract (LRT) (2012-2018) and invasive infections (1996-2018) sent to the Department of Clinical Microbiology were also included in this study. PCR was used for H. influenzae identification with hpd primers, and fucK primers for hpd-negative isolates. bexA primers were used for capsule detection, then further serotyped with serotype specific primers. Disk diffusion and E-tests were used to test for antibiotic susceptibility. The screening test from The Nordic Committee on Antimicrobial Susceptibility Testing was used for detection of β-lactam resistance mechanism(s), using benzylpenicillin unit 1 ...